Predictors of Relationship Autonomy: The Roles of Cognitive Flexibility and Psychological Capital - Turan , Selva; Kutsal , Ahmet; Billieux , Joel (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive roles of cognitive flexibility and psychological capital on relationship autonomy among couples.Methods and Materials: A cross-sectional design was employed with a sample of 203 participants, determined based on the Morgan and Krejcie table. Participants, all in committed romantic relationships, were recruited from community centers and online platforms. Data were collected using the Relationship Autonomy Scale (RAS), the Cognitive Flexibility Inventory (CFI), and the Psychological Capital Questionnaire (PCQ). Descriptive statistics, Pearson correlation analysis, and multiple regression analysis were conducted using SPSS version 27 to examine the relationships between the variables.Findings: The results indicated significant positive correlations between relationship autonomy and both cognitive flexibility (r = 0.48, p < 0.01) and psychological capital (r = 0.53, p < 0.01). Multiple regression analysis revealed that cognitive flexibility (B = 0.34, p < 0.001) and psychological capital (B = 0.47, p < 0.001) were significant predictors of relationship autonomy, accounting for 34% of the variance (R² = 0.34, F(2, 200) = 34.12, p < 0.001).Conclusion: The findings underscore the importance of cognitive flexibility and psychological capital in fostering relationship autonomy. These psychological resources enable individuals to navigate relational challenges effectively, supporting a balance between personal needs and relational interdependence.